The Thiocarboxanilide Nonnucleoside Inhibitor UC781 Restores Antiviral Activity of 3′-Azido-3′-Deoxythymidine (AZT) against AZT-Resistant Human Immunodeficiency Virus Type 1 - Borkow, Gadi (American Society for Microbiology, 1999)
N-[4-Chloro-3-(3-methyl-2-butenyloxy)phenyl]-2-methyl-3-furancarbothioamide (UC781) is an exceptionally potent nonnucleoside inhibitor of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase. We found that a 1:1 molar combination of UC781 and 3′-azido-3′-deoxythymidine (AZT) showed high-level synergy in inhibiting the replication of AZT-resistant virus, implying that UC781 can restore antiviral activity to AZT against AZT-resistant HIV-1. Neither the nevirapine plus AZT nor the 2′,5′-bis-O-(t-butyldimethylsilyl)-3′-spiro-5"-(4"-amino-1",2"-oxathiole-2",2"-dioxide plus AZT combinations had this effect. Studies with purified HIV-1 reverse transcriptase (from a wild type and an AZT-resistant mutant) showed that UC781 was a potent inhibitor of the pyrophosphorolytic cleavage of nucleotides from the 3′ end of the DNA polymerization primer, a process that we have proposed to be critical for the phenotypic expression of AZT resistance. Combinations of UC781 plus AZT did not act in synergy to inhibit the replication of either wild-type virus or UC781-resistant HIV-1. Importantly, the time to the development of viral resistance to combinations of UC781 plus AZT is significantly delayed compared to the time to the development of resistance to either drug alone.